Regionalism and centralism in the democratic restoration: the social movements performance - Arias Nieto, Custodio (2009)
In this essay, I expose, in broad outlines, the debate about descentralization between Mariátegui and Belaúnde, at the first part of the last century. Besides, I research the regionalization process established in the 1979 Constitution, especially, during the last decade. This period is caracterized by democracy restauration, the renewal of regionalization process and the reactivation of social conflicts.